Influencia de las entidades crediticias en el financiamiento microempresarial y su incidencia en el desarrollo del cantón Bolívar. - Alcívar Martínez, Benigno Javier (2011)
This thesis presents an overview of research and analysis has identified credit lines offered by banks and cooperatives in the area focused on the development of the productive sector 'through credit extended by financial institutions, credit histories are described there , identified the problem, the authors propose as a general objective to establish what is the influence of lenders in the financing and its impact on microenterprise development in that canton, and specific objectives: 1 .- Identify ways to qualify customers in banks and cooperatives to obtain credit. 2 .- To know the character credit financial products that can be found in the financial market. 3 .- To determine which of the banks is more than welcome to apply micro credits. 4 .- To determine whether the loan obtained by the micro was designed according to the needs of them. To carry out the fulfillment of these objectives was used interviews with managers of the canton lenders Bolivar and surveys to members of the Chamber of Commerce of the Ccanton Bolivar. Its implementation contributed to the effective study of the economic situation of the canton Bolivar and microenterprise development.